Population biology and vulnerability to fishing of deep‐water Eteline snappers. (10th January 2013) - Williams, A. J.; Loeun, K.; Nicol, S. J.; Chavance, P.; Ducrocq, M.; Harley, S. J.; Pilling, G. M.; Allain, V.; Mellin, C.; Bradshaw, C. J. A.
Summary Deep‐water fish in the tropical and sub‐tropical Pacific Ocean have supported important fisheries for many generations. Observations of localised depletions in some fisheries have raised concerns about the sustainability of current fishing rates. However, quantitative assessments of deep‐water stocks in the Pacific region have been limited by the lack of adequate biological and fisheries data. Estimates are provided of age‐based demographic parameters for two important deep‐water snapper species in the Pacific, Etelis carbunculus and E. coruscans. A spawner biomass‐per‐recruit (SPR) model was applied to determine fishing mortality rates for each species that would achieve specified biological targets (40% unexploited levels, SPR40) and limit (30% unexploited levels, SPR30) reference points, and examine the sensitivity of the model to variation in natural mortality and age at first capture. The maximum observed age, based on increment counts from sectioned otoliths, was 21 years for E. carbunculus and 18 years for E. coruscans. Total mortality (Z), estimated from the Hoenig regression, was 0.21 year−1 for E. carbunculus and 0.25 year−1 for E. coruscans. The best approximating growth models were the von Bertalanffy model (L∞ = 896 mm fork length, k = 0.28, t0 = 0.51) for E. carbunculus and the logistic model (L∞ = 879 mm fork length, k = 0.32 year−1, t0 = 3.42) for E. coruscans. The spawner biomass‐per‐recruit analysis demonstrated that lower rates of fishing mortality were required for E. coruscans than for E. carbunculus to maintain spawning biomass above estimated biological reference points. Estimates of spawner biomass‐per‐recruit were more sensitive to variation in natural mortality than in the age at first capture, suggesting that regulating fishing mortality rather than gear selectivity would be a more effective management measure for both species. Maintaining fishing mortality <0.1 for both species is recommended as a cautious approach to management, given the uncertainty in estimates of natural mortality and mixed fishery considerations.